Public space project, between complexity and ecological crisis – From challenge to opportunity for urban regeneration - Tommaso Berretta; Federico Desideri; Matteo Staltari (Agathón)
Contemporary times impose conditions of hypercomplexity, stemming from the overlap of contextual demands with the forces shaping the evolution of the landscape, which design disciplines are called upon to address. The field of investigation for this response is public space, a strategic area for experimenting with and challenging paradigms that cannot interpret current conditions of uncertainty and non-linearity. Starting from the current ecological crisis, the proposed approach abandons rigid formal structures, embracing scenarios with mutable and flexible outcomes. This perspective, already explored in case studies spanning landscape, urban design, and public space, becomes a paradigm to address complexities and design disorder, opening the way for a redefinition of design from both procedural and strategic viewpoints.